DEVELOPMENT OF INTERACTIVE E-MODULES FOR VOCATIONAL STUDENTS IN LEARNING MATHEMATICS TRIGONOMETRY MATERIAL - Ucik Fitri Handayani; Qissiissina Azzahro (ARITMATIKA: Jurnal Riset Pendidikan Matematika, 2024)
In the current technological era, the utilization of media in learning is needed to support the learning process of students. This research aims to develop interactive e-modules in the context of mathematics learning, especially on trigonometric material in right triangles. This research focuses on the involvement of technology to increase student motivation and learning outcomes. This research is a Research and Development (R&D) study or development research with a modified 4D (Define, Design, Develop, and Deseminate) research model into 3D. The research was conducted at SMKN 1 Gedangan in class X even semester. The results showed that the interactive e-module media was very valid as measured by the validity test of material and media experts by 87.5% or the value of Va-3.5, which means that the media is valid for use. The results of the practicality test obtained very practical criteria which amounted to 92.5%. The results of practicality by students obtained a result of 81.97% which means that the media is very practical to use. The results of the effectiveness test were obtained from the pretest and posttest results with a percentage increase of 84.615% and an N-gain value ≥0.7, which means that the media effectiveness level of the interactive e-module is very high. From the post-test results, it can be concluded that the interactive E-module is very effective in improving student learning outcomes through the use of appropriate and innovative technology.